Liver disease symptoms in non-alcoholic fatty liver disease and small intestinal bacterial overgrowth - Rafiei Rahmatollah; Bemanian Mahboobeh; Rafiei Fereshteh; Bahrami Mahmood; Fooladi Lotfollah; Ebrahimi Giti; Hemmat Ahmadreza; Torabi Zahra (Sciendo, 2018)
Introduction. It seems that there is a relationship between small intestinal bacterial overgrowth (SIBO) and non-alcoholic fatty liver disease (NAFLD). The main objective of this study was to evaluate the prevalence of SIBO among NAFLD patients.